Human capital: the key to knowledge management in public organizations. An integrative approach - Reis, Danisson Luiz dos Santos (2022)
This paper investigates how academic research addresses the relationship between human capital, knowledge management, and the public sector. To this end, an integrative review was carried out with key terms related to the three mentioned themes and conducted with data imported from the Scopus database. Among the results achieved, six clusters of thematic approach were identified. After the analysis mentioned above, it was possible to identify how human resources contribute to knowledge management in the public sector and the consequences for people resulting from its implementation. This article contributes to research on the importance of people in knowledge management in public organizations, promoting the synthesis of the most recent studies on the subject.